2000
DOI: 10.1111/j.1432-2277.2000.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary nitrate excretion associated with hepatic allograft rejection in experimental rat models and clinical cases

Abstract: Increased urinary nitrate excretion associated with hepatic allograft rejection in experimental rat models and clinical casesAbstract In this study, we investigated the relationship between excretion of urinary nitrate as a stable end-product of nitric oxide (NO) metabolism and hepatic allograft rejection. In experimental rat models, hepatic allograft rejection was associated with increased nitrate excretion with a peak on postoperative day 5. The severity of the hepatic allograft rejection was dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Increased endogenous NO production, represented by the rise in systemic nitrate levels, have been described during clinical hepatic allograft rejection 114–116. It was found that serum114 and urinary115 nitrate levels correlate well with the grade of allograft rejection in human liver transplantation. These results agree with the data reported during allograft rejection in animal models 117,118.…”
Section: Liver Transplantation and Hepatic Ischemia‐reperfusion Injurymentioning
confidence: 99%
“…Increased endogenous NO production, represented by the rise in systemic nitrate levels, have been described during clinical hepatic allograft rejection 114–116. It was found that serum114 and urinary115 nitrate levels correlate well with the grade of allograft rejection in human liver transplantation. These results agree with the data reported during allograft rejection in animal models 117,118.…”
Section: Liver Transplantation and Hepatic Ischemia‐reperfusion Injurymentioning
confidence: 99%